Manajemen Public Relations Indonesian Flag Football Association - Nurunnisa Nabilla Azhary; Dadan Mulyana (UNISBA Press, 2022)
Abstract. The Covid-19 pandemic has had a negative impact on the field of flag football, due to the limited space for team sports activities in open spaces. With these limitations, the Bandung Regional Indonesian Flag Football Association (IFFA) is still able to carry out its routine activities until it successfully organizes various events. Behind the success of the event during the current pandemic, it cannot be separated from the management of public relations and the communication process carried out by the Bandung Regional IFFA administrators with their stakeholders. This study focuses on how the management of PR IFFA Regional Bandung in increasing existence through the